Methodological proposal to analyze land use and land cover changes: the case of Santa Catarina state in Brazil from 2000 to 2010 - Mio de Souza, Juliana; Marques da Costa, Eduarda (Sustainability in Debate, 2020)
The objective of this paper is to verify the land use and land cover change and to relate them with the potential driving forces that have been acting in the state of Santa Catarina, Brazil, during the period from 2000 to 2010. The methodology consists in identifying trends in the land use and land cover change; indicating possible explanatory factors based in factorial analysis for main components and elaborating a final typology, based on cluster analysis. Results include a strong expansion and growing strength of agricultural activity as well as forestry throughout the state and the loss of native vegetation, which points to the need to develop protective actions and occupation and land use regulations, in particular, in the environmental area, encompassing the development of an intensive and mechanized agricultural activity.